Restructuring the PhD course in Drug Delivery for a better alignment and congruence - Thakur, Aneesh (Improving University Science Teaching and Learning, 2023)
The course alignment is important to establish the desired outcomes of teaching and learning in terms of contents as well students’ understanding (Biggs & Tang, 2003). Therefore, any gaps and misalignments in a curriculum should be identified. A means to identify the gaps or misalignment in teaching, learning, and evaluation is to delineate the congruence of their purposes, processes and content. Hounsell and Hounsell (2007) recognized six dimensions of congruence within teaching-learning environments in higher education: (i) congruence of course organization and management, (ii) congruence of teaching-learning activities, (iii) congruence of learning support, (iv) congruence of assessment and feedback, (v) congruence with students’ background and aspirations and (vi) congruence of curriculum, aims, scope and structure (Hounsell & Hounsell, 2007). Herein, the restructuring of alignment and congruence of Drug Delivery course is discussed in the context of students’ background knowledge and assessment and feedback.